Vaccine hesitancy about the HPV vaccine among French young women and their parents: a telephone survey - Fatima Gauna; Pierre Verger; Lisa Fressard; Marie Jardin; Jeremy K. Ward; Patrick Peretti-Watel (BMC, 2023)
Background The human papillomavirus (HPV) vaccine reduces the burden of cervical and other cancers. In numerous countries, a slow uptakeof this vaccine persists, calling for a better understanding of the structural factors leading to vaccine acceptation. We aimed to assess the attitudes toward HPV vaccination among its intended public to explore its specific characteristics. Methods A random cross-sectional telephone survey of the French general population provided data from a sample of 2426 respondents of the target public: the parents of young women and the young women aged 15-25 themselves. We applied cluster analysis to identify contrasting attitudinal profiles, and logistic regressions with a model averaging method to investigate and rank the factors associated with these profiles. Results A third of the respondents had never heard of HPV. However, most of the respondents who had heard of it agreed that it is a severe (93.8%) and frequent (65.1%) infection. Overall, 72.3% of them considered the HPV vaccine to be effective, but 54% had concerns about its side effects. We identified four contrasting profiles based on their perceptions of this vaccine: informed supporters, objectors, uninformed supporters, and those who were uncertain. In multivariate analysis, these attitudinal clusters were the strongest predictors of HPV vaccine uptake, followed by attitudes toward vaccination in general. Conclusions Tailored information campaigns and programs should address the specific and contrasted concerns about HPV vaccination of both young women and of their parents.